The Comparison of Modal Be Going to and Will Between English and Gorontalonese - Hamzah, Aryati (The Eastasouth Journal of Learning and Educations, 2024)
This study explores the differences and similarities in the use of modal expressions "be going to" and "will" between English and Gorontalonese, a language spoken in the Gorontalo region of Indonesia. The modal expressions "be going to" and "will" are commonly used in English to indicate future actions, intentions, or predictions. However, their usage may vary across languages and dialects. Through a comparative analysis of authentic language data, including texts and conversations, this research investigates how speakers of English and Gorontalonese employ these modal expressions in different contexts. The study examines factors such as grammatical structure, semantic nuances, and cultural influences that may contribute to the variation in the usage of "be going to" and "will" between the two languages. The findings provide insights into the linguistic features of modal expressions in English and Gorontalonese, shedding light on cross-linguistic differences and contributing to the field of comparative linguistics.